Electric power cyber-physical systems vulnerability assessment under cyber attack - Qu, Zhengwei; Sun, Wenting; Dong, Jie; Zhao, Jianjun; Li, Yang (Frontiers in Energy Research, 2023)
Improving the accuracy of the vulnerability assessment of the power cyber-physical system has important practical value for protecting the vulnerable links of the system and preventing large power outages. This article studies the vulnerability assessment of power cyber-physical systems under cyber-attacks. First, from the perspective of topology, the electrical betweenness is used as the structural vulnerability index of the power system. Based on the power flow characteristics of the power network, the voltage is used as the state vulnerability index. Then, starting from the structure, the node degree and clustering coefficient are selected to analyze the structural vulnerability. Considering the service transmission characteristics of the information system, the power service importance is selected as the vulnerability assessment index of the information system. The two selected indexes are used to construct a quantitative formula, and a comprehensive index is obtained to complete the node vulnerability assessment of the power information system. Then, on the basis of the system vulnerability assessment, we screen to determine the entry and target nodes of network attacks and predict the network attack path. Finally, the effectiveness of the proposed method for vulnerability assessment and feasibility is verified by MATLAB programming simulation.